Effect of boron spraying on some traits of two anise varieties (Baladi and Shami)pimpinella anisum L. under conditions of the (Al-Ghab) area. (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out in - Hama Governorate - Salhab region - for the agricultural season 2022-2023.In order to study the effect of boron spraying on some characteristics of two types of anise (Baladi and Shami), where four concentrations (0-25-50-75) mg/l were studied. By split cutting method for one time, and spraying with boron twice (the beginning of flowering and the beginning of the node), the averages were recorded, and the significant differences were calculated. (Baladi and Shami) as the type of model did not affect these characteristics. The results of the interaction in terms of the number of branches/plant between the studied cultivars (Baladi and Shami) and the studied concentrations of boron (0,25,50,75) mg/L indicated that there were significant differences between the studied treatments and the control. Where the interaction between the concentration of 25 mg/L and the local anise variety achieved a significant superiority over the rest of the treatments and the control, and achieved the highest value (26.35) branch compared to the control, which achieved the lowest value (15.21) branch for the Levantine variety. The results of the interaction in terms of fruit/plant weight between the studied cultivars (Baladi and Shami) and the studied concentrations of boron (0,25,50,75) mg/l showed significant differences between the treatments and the control, and the interaction between the concentration was 25 mg/l and the anise baladi. Moral superiority over the rest of the transactions and the control.